Postpartum Ovarian Activity and Sexual Behavior in Swamp Buffalo (Bubalus bubalis) - Yindee , M.; Techakumphu , M.; Lohachit , C.; Sirivaidyapong , S.; Na-Chiangmai , A.; Colenbrander , B. (Advanced Research in Biological Science Vol. 6, 2023)
Postpartum follicular activity and sexual behavior were assessed in tropical conditions among swamp buffaloes (Bubalus bubalis). Sixteen multiparous swamp buffaloes, aged 4-12 years (weighing between 432-676 kg), were observed starting from 5-29 days after giving birth. Ovarian follicular activity was daily monitored using a real-time B-mode linear array ultrasound scanner (Aloka SSD-500, Tokyo, Japan) equipped with a 7.5 MHz transrectal transducer. Estrous detection involved personal observation, video recording, and assessment of vaginal discharge. Uterine involution averaged 28.74+1.21 days (mean + SEM, range 22-41 d, n=16). Before the first ovulation, follicular activity followed a wave-like pattern. There were no significant differences in follicular growth rates and maximum follicle diameter in the second, third, and fourth postpartum cycles, whereas the first ovulation's follicular growth was notably lower (p<0.05). Short ovarian cycles were observed in 93.3% of buffaloes between the first and second ovulation (10.14+40 d) and in 50.0% between the second and third ovulation (12.00+1.53 d). However, one buffalo experienced a longer estrus cycle lasting 27 days. Behavioral indicators of estrus following the first postpartum ovulation were less conspicuous compared to subsequent ovulations. For optimal reproductive efficiency, swamp buffaloes should ideally be bred between 1 to 2 months postpartum during the second ovulation.